Digitalizing informed consent in healthcare: a scoping review - Mascha Goldschmitt; Patricia Gleim; Sekina Mandelartz; Philipp Kellmeyer; Thomas Rigotti (BMC Health Services Research)
Abstract Background Traditional paper-based informed consent for medical procedures poses a number of challenges, such as low comprehensibility, lack of customization, and limited time for discussion with medical staff. Digitalization, especially in light of the rapid development of AI-based technologies, could provide a solution. Methods This scoping review explores the digitalization of the consent process, focusing on the types of technologies used, their role in the consent process, evaluation results, and success factors for implementation. Following the guidance of the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis for scoping reviews, we searched various databases and platforms (Web of Science, EBSCOHost, PubMed and PubPsych) for eligible articles published between January 2012 and June 2024. Results Title and abstract screening of 4287 records resulted in the inclusion of 27 studies for analysis. The findings suggest that digitalizing the consent process can enhance recipients' understanding of clinical procedures, potential risks and benefits, and alternative treatments. Mixed evidence exists on patient satisfaction, convenience, and perceived stress. The limited research on healthcare professionals indicates that time savings are the major benefit. AI-based technologies seem to be not yet suitable for use without medical oversight. Conclusions Overall, few interactive technologies have been evaluated in the patient consent process, and only recently have studies started to examine the use of AI technologies. This indicates an early stage of the digitalization of patient consent for medical diagnosis and treatment. However, there is great potential to optimize the consent process for both patients and healthcare professionals. Methodologically sound studies are needed to validate these findings. Trial registration The scoping review was initially preregistered with PROSPERO (CRD42023397681) as a systematic review. The reasons for the change to a scoping review are outlined in the registration, while the systematic approach to data extraction and analysis was maintained.